Om den svenska postmodernismen - Zeidler Källström, Lisa (Folia Scandinavica Posnaniensia, 2007)
It is highly characteristic of the Swedish postmodern fiction that it is trying to destroy the differences between pure fiction and reahty, between the action taking place and the narration itself, only the bare bone hyperreality should remain. The meetings between the fictitious and the real existing persons must be seen as an attempt to take a fmal step beyond this border. There exists no absolute truth and that is the reason why there cannot be any lie, there is nothing left but the authentic, autistic narration, which can sometimes be autobiographic or horrifying, but always referring to other already written literature.